Citra Diri dan Motif: Fenomena Perempuan Bertato di Kota Metropolitan Jakarta - Ballian Siregar; Aurora Amira; Ruslan Ramli; Erna Febriani (Avant Garde, 2023)
This study was intended to determine the relationship between self-image and tattooed women who live in the metropolitan city of Jakarta. The purpose of this study was to examine the meaning of symbolic communication and the self-image built by tattooed women in the metropolitan city of Jakarta. The grand theory used in this research is George Herbert Mead's theory of symbolic interaction and also the theory of self-image. The research method used is a qualitative approach with a phenomenological perspective. The interviewees were ten women with tattoos, using the snowball sampling technique. This research has succeeded in revealing several factors of women's motives with tattoos, e.g., tattoos as works of art, media for self-expression, expressions of depression, history, spirituality, and pleasure only. The conclusion of this study is that tattooed women believe that tattoos can form a positive self-image because, with tattoos, they can increase self-confidence and get to know themselves better. These tattooed women do not want a negative view of their tattoos because not all tattooed women are criminals or have deviant behavior. The implication of this research is that women with tattoos do not need to hear negative views from other people and can build a good self-image for themselves; thus, their tattoos are not underestimated by other people.